Pelatihan Pembuatan Pembangkit Listrik Energi Baru Terbarukan di SMK Negeri 7 Kota Pontianak - Hadary, Ferry; Saziati, Ochih (Indonesian Journal for Social Responsibility, 2024)
Indonesia has enormous potential for new renewable energy (EBT), but it has not been followed up with optimal utilization and energy saving behavior is still very low in everyday life. The introduction of EBT-based learning media in the form of solar power plants (PLTS), hydroelectric power plants (PLTA) and wind power plants (PLTB) is the technology that is most easily applied to all groups in various sectors, especially in the education sector. Utilization of PLTS, PLTA and PLTB technology requires human resources (HR) who have the competence to manage it. So this Community Service Activity (PKM) program proposes training in creating an EBT power plant at SMK Negri 7 Pontianak as a means to support human resources in understanding energy conservation and the use of EBT. The learning media consists of a PLTS display with a photovoltaic system, a PLTA display with a mini turbine connected to a dynamo and a PLTB display which utilizes the power of wind gusts to rotate a turbine which is then connected directly to a generator so that each display device produces electrical energy. Methods for carrying out activities include implementation and socialization of learning media. From the results of the presentation and training on making EBT power plants, students and teachers were enthusiastic about hearing and gaining new understanding and skills regarding the use of EBT technology in the form of learning media.